1989
DOI: 10.1111/j.1526-4610.1989.hed2901015.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow and Vascular Reactivity During Attacks of Classic Migraine'Limitations of the Xe‐133 Intraarterial Technique

Abstract: The present study reports cerebral blood flow (CBF) measurements in 11 patients during attacks of classic migraine (CM)--migraine with aura. In 6 and 7 patients, respectively, cerebral vascular reactivity to increased blood pressure and to hypocapnia was also investigated during the CM attacks. The Xenon-133 intraarterial injection technique was used to measure CBF. In this study, based in part on previously published data, methodological limitations, in particular caused by scattered radiation (Compton scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 16 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Recently, research has focused on the role of neural dysfunction in the occurrence of migraines, with reports suggesting associations with dysfunction of the sympathetic nervous system 7 and dysfunction in the brainstem related to modulation of craniovascular afferents. 9 Previous studies have reported reduced cerebral blood flow during the aura phase among those with migraine with aura 10,11 and the persistence of reduced cerebral blood flow into the pain phase of migraine. 3 Wolff's "vascular theory" suggests vasoconstriction of intracerebral ar-teries leads to ischemia and symptoms of aura and a subsequent hyperemic response leads to vasodilation and headache pain.…”
mentioning
confidence: 96%
“…Recently, research has focused on the role of neural dysfunction in the occurrence of migraines, with reports suggesting associations with dysfunction of the sympathetic nervous system 7 and dysfunction in the brainstem related to modulation of craniovascular afferents. 9 Previous studies have reported reduced cerebral blood flow during the aura phase among those with migraine with aura 10,11 and the persistence of reduced cerebral blood flow into the pain phase of migraine. 3 Wolff's "vascular theory" suggests vasoconstriction of intracerebral ar-teries leads to ischemia and symptoms of aura and a subsequent hyperemic response leads to vasodilation and headache pain.…”
mentioning
confidence: 96%
“…Studies of rCBF with intra-arterial or inhaled l33Xe have shown a quite consistent pattern of cortical oligemia in the prodromal phase of classic migraine, extending into the headache phase, followed by hyperper fusion lasting well beyond the cessation of pain [13][14][15][16][17][18]. Opinions have diverged, however, in the interpretation of the spreading oligemia of the prodromal phase.…”
Section: Discussionmentioning
confidence: 99%
“…Opinions have diverged, however, in the interpretation of the spreading oligemia of the prodromal phase. In fact, some authors view it as purely secondary to decreased neuronal function and hence reflecting a metabolic de pression of the rCBF [14,15], whereas others argue that contraction of cortical arterioles plays a crucial role and therefore true ischemia is the pathophysiological mecha nism [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…15 Their data indicate that cerebral blood flow decreases focally to values of 20ml/100gm/min during the initial portion of the attack. Regional cortical blood flow in patients is measured most frequently using Xenon-133 washout following intravenous or intra-arterial injection of the isotope.…”
Section: Introductionmentioning
confidence: 98%